Wood Quality Assessment of Populus deltoides Clones from Haldwani, Uttaranchal - Kothiyal, Vimal; Khanduri, A. K; Jain, V. K. (Indian Forester, 2005)
Strength properties of 12 clones of 10’ years old Populus deltoides from single trees obtained from Haldwani (Uttaranchal), India are reported. The preliminary results on strength properties for screening the clones for timber indicated that at Haldwani, clone number 290/84 has the highest specific gravity and strength properties. Clone number 75/84 has the lowest values among all the 12 clones tested.